SARMIENTO MÉNDEZ, Xosé Antón (Coord.) (2016). Manual AELPA del Parlamentario. Madrid: Wolters Kluwer (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2016)
Recensión de la obra: SARMIENTO MÉNDEZ, Xosé Antón (Coord.) (2016). Manual AELPA del Parlamentario. Madrid: Wolters Kluwer.